Lithium sulfur battery and method for manufacturing lithium sulfur battery
The lithium sulfur battery design, featuring a sulfide solid electrolyte in the first layer and a polymer electrolyte in the second layer, addresses the issue of short circuits and capacity reduction by accommodating the expansion and contraction of the positive electrode layer, resulting in effective short circuit suppression and high battery capacity.
Patent Information
- Application Number
- JP2023180477
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-10-19
AI Technical Summary
Solid electrolyte layers in lithium sulfur batteries face challenges in following the expansion and contraction of the positive electrode layer during charging and discharging, leading to cracks and short circuits, while attempts to prevent short circuits may result in reduced battery capacity.
A lithium sulfur battery design incorporating a first solid electrolyte layer with a sulfide solid electrolyte and a second solid electrolyte layer with a polymer electrolyte and/or gel electrolyte, allowing the battery to suppress short circuits and maintain high capacity.
The proposed battery design effectively suppresses short circuits associated with charge and discharge while achieving a high battery capacity, as the flexible polymer electrolyte layer in the second solid electrolyte can accommodate the expansion and contraction of the positive electrode layer.
Smart Images

Figure 2025070279000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to lithium-sulfur batteries and methods for making lithium-sulfur batteries. [Background technology]
[0002] Lithium-sulfur batteries use sulfur as the positive electrode active material, and are attracting attention as next-generation batteries because sulfur has a high theoretical capacity. In liquid-type lithium-sulfur batteries, capacity degradation occurs due to the elution of lithium polysulfides into the electrolyte, so solid-state lithium-sulfur batteries that include a solid electrolyte layer have been developed, and the following solid-state lithium-sulfur batteries are known:
[0003] For example, Patent Document 1 discloses an all-solid-state battery having a first electrode layer, a first solid electrolyte layer, a second solid electrolyte layer, and a second electrode layer in this order, the first solid electrolyte layer having a first surface, the second solid electrolyte layer having a second surface in contact with the first surface, and a maximum height Rz1 of the first surface and a maximum height Rz2 of the second surface satisfying the following predetermined relationship: According to the all-solid-state battery of Patent Document 1, even if a crack occurs in one of the first solid electrolyte layer and the second solid electrolyte layer, the crack is likely to be prevented from propagating to the other layer, and excellent short-circuit resistance is likely to be ensured. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2023-009988 A Summary of the Invention [Problem to be solved by the invention]
[0005] Although a solid electrolyte layer containing a sulfide solid electrolyte has excellent properties as a solid electrolyte layer, it cannot follow the expansion and contraction of a cathode layer containing sulfur during charging and discharging, and the solid electrolyte layer may crack, which may cause a short circuit. In addition, if a solid electrolyte layer that follows the expansion and contraction is used to prevent a short circuit, the capacity may be significantly reduced. Therefore, further improvement of the solid electrolyte layer in a lithium-sulfur battery is required.
[0006] Therefore, an object of the present disclosure is to provide a lithium-sulfur battery that can suppress short circuits caused by charging and discharging and can obtain a high battery capacity. [Means for solving the problem]
[0007] The present disclosure achieves the above object by the following means.
[0008] A lithium-sulfur battery comprising: the lithium-sulfur battery has a positive electrode layer, a first solid electrolyte layer, a second solid electrolyte layer, and a negative electrode layer in this order; The first solid electrolyte layer includes a sulfide solid electrolyte; and The second solid electrolyte layer comprises a polymer electrolyte and / or a gel electrolyte; Lithium-sulfur battery. <Aspect 2> The negative electrode layer has a negative electrode current collector layer, and Lithium ions that have migrated from the positive electrode layer during charging are precipitated as metallic lithium between the second solid electrolyte layer and the negative electrode current collector layer. 2. The lithium-sulfur battery of embodiment 1. Aspect 3: The lithium-sulfur battery of aspect 1 or 2, wherein the second solid electrolyte layer includes a polymer electrolyte. <Aspect 4> The lithium-sulfur battery according to any one of Aspects 1 to 3, wherein the polymer electrolyte contains polyethylene oxide. A method for producing the lithium-sulfur battery according to any one of Aspects 1 to 4, comprising the steps of: laminating a preliminary positive electrode layer containing sulfur and a sulfide containing phosphorus and sulfur, the first solid electrolyte layer, the second solid electrolyte layer, and the negative electrode layer in this order to form a preliminary laminate; A discharge operation is performed on the preliminary laminate, whereby a part of the sulfur in the preliminary positive electrode layer, as well as a sulfide containing phosphorus and sulfur elements, are reacted with lithium to produce a sulfide solid electrolyte, thereby forming the positive electrode layer. Effect of the Invention
[0009] The lithium-sulfur battery of the present disclosure can suppress short circuits that occur during charging and discharging, and can obtain a high battery capacity. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic diagram illustrating a lithium-sulfur battery according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, the embodiments of the present disclosure will be described in detail. Note that the present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the gist of the present disclosure. In addition, in the description of the drawings, the same elements are given the same reference numerals, and duplicated descriptions will be omitted.
[0012] The lithium-sulfur battery of the present disclosure is a solid-state battery having a solid electrolyte layer as an electrolyte layer. Note that, in the context of the present disclosure, a "solid-state battery" refers to a battery that uses at least a solid electrolyte as an electrolyte, and therefore a solid-state battery may use a combination of a solid electrolyte and a liquid electrolyte as an electrolyte.
[0013] In the present disclosure, a "composite" refers to a composition that can form a positive electrode (negative electrode) layer or a solid electrolyte layer as it is or by further containing other components. Also, in the present disclosure, a "composite slurry" refers to a slurry that contains a dispersion medium in addition to a "composite" and can be applied and dried to form a positive electrode (negative electrode) layer or a solid electrolyte layer.
[0014] Lithium-sulfur battery The lithium-sulfur battery of the present disclosure comprises: a positive electrode layer, a first solid electrolyte layer, a second solid electrolyte layer, and a negative electrode layer, in this order; The first solid electrolyte layer includes a sulfide solid electrolyte; and The second solid electrolyte layer includes a polymer electrolyte and / or a gel electrolyte.
[0015] The lithium-sulfur battery of the present disclosure can suppress short circuits that occur during charging and discharging, and can obtain a high battery capacity.
[0016] 1, the lithium-sulfur battery of the present disclosure specifically includes a positive electrode layer 110, a first solid electrolyte layer 210 including a sulfide solid electrolyte, a second solid electrolyte layer 220 including a polymer electrolyte and / or a gel electrolyte, and a negative electrode layer 310. When the battery is charged and discharged, the positive electrode layer 110 including sulfur as a positive electrode active material expands and contracts.
[0017] The lithium-sulfur battery of the present disclosure has a second solid electrolyte layer containing a polymer electrolyte and / or a gel electrolyte. Since the second solid electrolyte layer contains a polymer electrolyte layer and / or a gel electrolyte layer, it is relatively flexible and can follow the expansion and contraction of the sulfur-containing positive electrode layer during charging and discharging, which is presumably why short circuits can be suppressed.
[0018] In addition, the lithium-sulfur battery of the present disclosure has a first solid electrolyte layer containing a sulfide solid electrolyte between the positive electrode layer and the second solid electrolyte layer containing a polymer electrolyte and / or a gel electrolyte. Since the first solid electrolyte layer is a sulfide solid electrolyte, it is presumed that the barrier to lithium insertion into the positive electrode layer can be reduced, thereby enabling the lithium-sulfur battery to obtain a high battery capacity.
[0019] <Configuration of lithium-sulfur battery> The lithium-sulfur battery of the present disclosure has, in this order, a positive electrode layer, a first solid electrolyte layer, a second solid electrolyte layer, and a negative electrode layer.
[0020] <Positive electrode layer> The positive electrode layer includes at least a positive electrode active material. During charging of the battery, lithium ions move from the positive electrode active material through the first solid electrolyte layer and the second solid electrolyte layer to the negative electrode layer. During discharging of the battery, lithium in the negative electrode layer is ionized and returned to the positive electrode active material. The positive electrode layer includes a positive electrode active material layer and an optional positive electrode current collector layer.
[0021] <Positive electrode current collector layer> The material used for the positive electrode current collector layer is not particularly limited, but may be any material commonly used as a positive electrode current collector for lithium-sulfur batteries. Examples of materials used for the positive electrode current collector layer include, but are not limited to, Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, etc. The positive electrode current collector layer may have a coating layer on its surface for the purpose of adjusting resistance, etc. The positive electrode current collector layer may be a metal foil or a substrate on which the above metal is plated or vapor-deposited.
[0022] The shape of the positive electrode current collector layer is not particularly limited, but examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred.
[0023] The thickness of the positive electrode current collector layer is not particularly limited, but may be 0.1 μm or more, or 1 μm or more, and may be 1 mm or less, or 100 μm or less.
[0024] <Cathode active material layer> The positive electrode active material layer contains at least sulfur as a positive electrode active material, and may further contain, optionally, a conductive assistant, a binder, a solid electrolyte, and the like. The positive electrode active material layer may also contain various other additives. The contents of the positive electrode active material, conductive assistant, binder, solid electrolyte, and the like in the positive electrode active material layer may be appropriately determined according to the intended battery performance. For example, the content of the positive electrode active material may be 40% by mass or more, 50% by mass or more, 60% by mass or more, or 100% by mass or less, or 90% by mass or less, assuming that the entire positive electrode active material layer (total solid content) is 100% by mass.
[0025] (Cathode active material) As described above, at least sulfur is used as the positive electrode active material. The sulfur may be elemental sulfur or a sulfur compound as long as it can function as a positive electrode active material.
[0026] The positive electrode active material layer may contain a positive electrode active material other than elemental sulfur or a sulfur compound. Examples of positive electrode active materials other than elemental sulfur or a sulfur compound include various lithium-containing compounds. Examples of lithium-containing compounds include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganate (LiMn2O4), lithium nickel-cobalt-manganese oxide (NCM), LiCO 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, Lithium nickel-cobalt-aluminate (NCA; LiNi x Co y Al z O2), Li 1+x Mn 2-x-y M y The material may be, but is not limited to, a Li-Mn spinel substituted with a different element having a composition represented by O4 (M is one or more metal elements selected from Al, Mg, Co, Fe, Ni, and Zn).
[0027] The ratio of elemental sulfur and the sulfur compound contained in the positive electrode active material layer is not particularly limited, and may be 50% by mass to 100% by mass, 60% by mass to 100% by mass, 70% by mass to 100% by mass, 80% by mass to 100% by mass, or 90% by mass to 100% by mass with respect to the positive electrode active material layer.
[0028] The shape of the positive electrode active material is not particularly limited as long as it is a general shape for a positive electrode active material of a lithium-sulfur battery. The positive electrode active material may be, for example, particulate. The positive electrode active material may be solid, hollow, void-containing, or porous. The positive electrode active material may be primary particles, or may be secondary particles formed by agglomeration of a plurality of primary particles. The average particle diameter D of the positive electrode active material 50 The average particle size D may be, for example, 1 nm or more, 5 nm or more, or 10 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less. 50 is the particle size (median size) at an integrated value of 50% in the volume-based particle size distribution determined by a laser diffraction / scattering method.
[0029] (Conductive assistant) The conductive assistant is not particularly limited. The conductive assistant may be, for example, vapor grown carbon fiber (VGCF), acetylene black (AB), Ketjen black (KB), carbon nanotube (CNT), carbon nanofiber (CNF), etc., but is not limited thereto. The conductive assistant may be, for example, particulate or fibrous, and its size is not particularly limited. The conductive assistant is not particularly limited, but may be used alone or in combination of two or more kinds.
[0030] (Binder) The binder is not particularly limited. The binder may be, for example, polyvinylidene fluoride (PVdF), butadiene rubber (BR), polytetrafluoroethylene (PTFE), styrene butadiene rubber (SBR), etc., but is not limited thereto. The binder is not particularly limited, but may be used alone or in combination of two or more.
[0031] (solid electrolyte) The material of the solid electrolyte is not particularly limited, and may be a sulfide solid electrolyte, an oxide solid electrolyte, a polymer electrolyte, or the like.
[0032] For the sulfide solid electrolyte, see the description of "First solid electrolyte layer" below. For the polymer electrolyte, see the description of "Second solid electrolyte layer" below.
[0033] An example of an oxide solid electrolyte is Li7La3Zr2O 12 , Li 7-x La3Zr 1-x Nb x O 12 , Li 7-3x La3Zr2Al x O 12 , Li 3x La 2 / 3-x TiO3, Li 1+x Al x Ti 2-x (PO4)3, Li 1+x Al x Ge 2-x (PO4)3, Li3PO4, or Li 3+x PO 4-x N x (LiPON), but is not limited to these.
[0034] The oxide solid electrolyte may be glass or crystallized glass (glass ceramics).
[0035] The shape of the positive electrode active material layer is not particularly limited, and may be, for example, a sheet-like positive electrode active material layer having a substantially flat surface. The thickness of the positive electrode active material layer is not particularly limited, and may be, for example, 0.1 μm or more, 1 μm or more, or 10 μm or more, and may be 2 mm or less, 1 mm or less, or 500 μm or less.
[0036] The positive electrode layer can be manufactured by applying a known method. For example, the positive electrode active material layer can be easily formed by dry or wet forming a positive electrode mixture containing the above-mentioned various components. The positive electrode active material layer may be formed together with the positive electrode current collector layer, or may be formed separately from the positive electrode current collector layer.
[0037] <First solid electrolyte layer> In the lithium-sulfur battery of the present disclosure, the first solid electrolyte layer includes a sulfide solid electrolyte.
[0038] The first solid electrolyte layer contains a sulfide solid electrolyte, and may further contain an optional binder and the like.
[0039] (Sulfide solid electrolyte) Examples of sulfide solid electrolytes include, but are not limited to, sulfide-based amorphous solid electrolytes, sulfide-based crystalline solid electrolytes, and argyrodite-type solid electrolytes. Specific examples of sulfide solid electrolytes include Li2S-P2S5-based (Li7P3S 11 , Li3PS4, Li8P2S9, etc.), Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-P2S5-GeS2(Li 13 GeP3S 16 , Li 10 GeP2S 12 ), LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li 7-x P.S. 6-x Cl x etc.; or combinations thereof, but are not limited to these.
[0040] The sulfide solid electrolyte may be glass or crystallized glass (glass ceramics).
[0041] For the binder, the description in the above "Positive electrode active material layer" can be referred to.
[0042] The thickness of the first solid electrolyte layer is not particularly limited, and may be, for example, 0.1 μm or more, 1 μm or more, or 10 μm or more, and may be 2 mm or less, 1 mm or less, or 500 μm or less.
[0043] The first solid electrolyte layer can be easily formed, for example, by dry or wet molding an electrolyte mixture containing the above-mentioned sulfide solid electrolyte and a binder and the like.
[0044] <Second solid electrolyte layer> In the lithium-sulfur battery of the present disclosure, the second solid electrolyte layer includes a polymer electrolyte and / or a gel electrolyte. The second solid electrolyte layer is not particularly limited, but preferably includes a polymer electrolyte.
[0045] (Polymer electrolyte) The polymer electrolyte refers to an electrolyte in which the content of a solvent component is 5% by mass or less. The content of the solvent may be 3% by mass or less, or may be 1% by mass or less.
[0046] The polymer electrolyte contains at least a polymer component. Examples of the polymer component include, but are not limited to, polyether-based polymers, polyester-based polymers, polyamine-based polymers, polysulfide-based polymers, etc. From the viewpoint of ion conductivity and mechanical properties such as Young's modulus, polyether-based polymers are preferred.
[0047] The polyether polymer is not particularly limited, but is preferably polyethylene oxide, that is, the polymer electrolyte is not particularly limited, but preferably contains polyethylene oxide.
[0048] The polyether polymer is not particularly limited, but preferably has a polyether structure in the main chain of the repeating unit. Examples of the polyether structure include, but are not limited to, a polyethylene oxide (PEO) structure and a polypropylene oxide (PPO) structure.
[0049] The polyether polymer is not particularly limited, but preferably has a PEO structure as a main repeating unit. The ratio of the PEO structure may be, for example, 50 to 100 mol%, 60 to 100 mol%, 70 to 100 mol%, 80 to 100 mol%, or 90 to 100 mol%. The polyether polymer may be, for example, a homopolymer or copolymer of an epoxy compound (e.g., ethylene oxide, propylene oxide).
[0050] The polymer component may have the following ion-conductive units: Examples of the ion-conductive units include polyethylene oxide, polypropylene oxide, polymethacrylic acid ester, polyacrylic acid ester, polydimethylsiloxane, polyacrylic acid, polymethacrylic acid, polyethylene vinyl acetate, polyimide, polyamine, polyamide, polyalkyl carbonate, polynitrile, polyphosphazene, polyolefin, and polydiene.
[0051] The weight average molecular weight of the polymer component is not particularly limited, but is, for example, 1,000,000 to 10,000,000 or less. The weight average molecular weight can be determined by gel permeation chromatography (GPC).
[0052] The polymer electrolyte may be used alone as a polymer component, or may be used in combination of two or more kinds. The polymer electrolyte may be a crosslinked polymer electrolyte in which the polymer component is crosslinked, or may be an uncrosslinked polymer electrolyte in which the polymer component is not crosslinked.
[0053] The polymer electrolyte may contain a supporting salt (lithium salt). The supporting salt (lithium salt) is not particularly limited, but may be an inorganic lithium salt, an organic lithium salt, or the like. The inorganic lithium salt may be, for example, LiPF6, LiBF4, LiClO4, LiAsF6, or the like, but is not limited to this case. The organic lithium salt may be, for example, LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(FSO2)2, LiC(CF3SO2)3, or the like, but is not limited to this case. For example, when the polymer electrolyte has an EO unit (C2H5O unit), the EO unit may be, for 1 mol part of the supporting salt, not particularly limited, 5 mol parts or more, 10 mol parts or more, or 15 mol parts or more, or 40 mol parts or less, or 30 mol parts or less.
[0054] (Gel electrolyte) The gel electrolyte contains an electrolytic solution in addition to a polymer electrolyte.
[0055] (electrolyte) The electrolyte solution is not particularly limited, but preferably contains a supporting salt and a solvent. For the supporting salt, the description in "(Polymer electrolyte)" above can be referred to.
[0056] The solvent used in the electrolytic solution is not particularly limited, but may include cyclic carbonates, chain carbonates, etc. Examples of cyclic carbonates include, but are not limited to, ethylene carbonate (EC), propylene carbonate (PC), but are not limited to, ethylene carbonate (BC), etc. Examples of chain carbonates include, but are not limited to, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), etc. Examples of solvents include, but are not limited to, acetates such as methyl acetate and ethyl acetate, and ethers such as 2-methyltetrahydrofuran, etc. Examples of solvents include, but are not limited to, γ-butyl lactone, sulfolane, N-methylpyrrolidone (NMP), 1,3-dimethyl-2-imidazolidinone (DMI), etc. Examples of solvents include, but are not limited to, γ-butyl lactone, sulfolane, N-methylpyrrolidone (NMP), 1,3-dimethyl-2-imidazolidinone (DMI), etc. Examples of solvents may be water.
[0057] The thickness of the second solid electrolyte layer is not particularly limited, and may be, for example, 0.1 μm or more, 1 μm or more, or 10 μm or more, and may be 2 mm or less, 1 mm or less, or 500 μm or less.
[0058] The second solid electrolyte layer can be easily formed, for example, by dissolving the above-mentioned polymer electrolyte and / or gel electrolyte, a supporting salt, etc. in a solvent and molding the second solid electrolyte layer precursor solution containing the above-mentioned various components.
[0059] <Negative electrode layer> The negative electrode layer may include only the negative electrode current collector layer, or may include the negative electrode active material layer and the negative electrode current collector layer. Lithium ions that migrate from the positive electrode during charging of the battery may receive electrons and precipitate as metallic lithium between the second solid electrolyte layer and the negative electrode current collector layer. Lithium ions that migrate from the positive electrode during charging of the battery may receive electrons and be retained in the negative electrode active material of the negative electrode active material layer. When discharging the battery, lithium in the negative electrode layer is ionized and returned to the positive electrode layer.
[0060] <Negative electrode active material layer> The negative electrode active material layer contains at least a negative electrode active material, and may further contain, optionally, a conductive assistant, a binder, a solid electrolyte, and the like. The negative electrode active material layer may also contain various other additives. The contents of the negative electrode active material, the conductive assistant, the binder, the solid electrolyte, and the like in the negative electrode active material layer may be appropriately determined according to the intended battery performance. For example, the content of the negative electrode active material may be 40% by mass or more, 50% by mass or more, or 60% by mass or more, and may be 100% by mass or less, or 90% by mass or less, assuming that the entire negative electrode active material layer (total solid content) is 100% by mass.
[0061] (Negative electrode active material) As the negative electrode active material, various materials can be adopted that have a potential (charge / discharge potential) for absorbing and releasing lithium ions that is lower than the positive electrode active material of the present disclosure. The material of the negative electrode active material is not particularly limited, and may be metallic lithium, or may be a material capable of absorbing and releasing metal ions such as lithium ions. Examples of materials capable of absorbing and releasing metal ions such as lithium ions include, but are not limited to, alloy-based negative electrode active materials and carbon materials. Among them, the material of the negative electrode active material is not particularly limited, but metallic lithium is preferred.
[0062] The alloy-based negative electrode active material is not particularly limited, and examples thereof include Si alloy-based negative electrode active materials and Sn alloy-based negative electrode active materials. The Si alloy-based negative electrode active material includes silicon, silicon oxide, silicon carbide, silicon nitride, and solid solutions thereof. The Si alloy-based negative electrode active material can include metal elements other than silicon, such as Fe, Co, Sb, Bi, Pb, Ni, Cu, Zn, Ge, In, Sn, Ti, and the like. The Sn alloy-based negative electrode active material can include tin, tin oxide, tin nitride, and solid solutions thereof. The Sn alloy-based negative electrode active material can include metal elements other than tin, such as Fe, Co, Sb, Bi, Pb, Ni, Cu, Zn, Ge, In, Ti, Si, and the like.
[0063] The carbon material is not particularly limited, and examples thereof include hard carbon, soft carbon, graphite, and the like.
[0064] The shape of the negative electrode active material is not particularly limited, but may be any shape that is common to negative electrode active materials for lithium-sulfur batteries. The negative electrode active material may be, for example, in a sheet form or in a particulate form. The negative electrode active material may involve lithium precipitation during charging, or may involve lithium dissolution during discharging. In this case, the negative electrode active material layer may be a layer made of metallic lithium or a lithium alloy (for example, metallic lithium foil or lithium alloy foil).
[0065] For the conductive assistant, binder, and solid electrolyte that can be contained in the negative electrode active material layer, the description in the above "<Positive electrode active material layer>" can be referred to.
[0066] The shape of the negative electrode active material layer is not particularly limited, and may be, for example, a sheet-like negative electrode active material layer having a substantially flat surface. The thickness of the negative electrode active material layer is not particularly limited, and may be, for example, 0.1 μm or more, 1 μm or more, or 10 μm or more, and may be 2 mm or less, 1 mm or less, or 500 μm or less.
[0067] <Negative electrode current collector> The material used for the negative electrode current collector layer is not particularly limited, but may be any material commonly used as a negative electrode current collector for lithium-sulfur batteries. Examples of materials used for the negative electrode current collector layer include, but are not limited to, Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, or a carbon sheet. In particular, from the viewpoint of ensuring reduction resistance and being difficult to alloy with lithium, the material used for the negative electrode current collector layer may contain at least one metal selected from Cu, Ni, and stainless steel, or may be made of a carbon sheet. The negative electrode current collector layer may have some kind of coating layer on its surface for the purpose of adjusting resistance, etc.
[0068] The shape of the negative electrode current collector layer is not particularly limited, but examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred.
[0069] The thickness of the negative electrode current collector layer is not particularly limited, but may be 0.1 μm or more, or 1 μm or more, and may be 1 mm or less, or 100 μm or less.
[0070] The negative electrode layer can be manufactured by applying a known method. For example, the negative electrode active material layer can be easily formed by dry or wet molding of a negative electrode mixture containing the above-mentioned various components. The negative electrode active material layer may be formed together with the negative electrode current collector layer or may be formed separately from the negative electrode current collector layer.
[0071] FIG. 1 is a schematic diagram illustrating one non-limiting embodiment of a lithium-sulfur battery of the present disclosure.
[0072] The lithium-sulfur battery 100 in FIG. 1 has a structure in which a positive electrode layer 110, a first solid electrolyte layer 210, a second solid electrolyte layer 220, and a negative electrode layer 310 are laminated. The positive electrode layer 110 contains sulfur, and the first solid electrolyte layer 210 contains a sulfide solid electrolyte. The second solid electrolyte layer 220 contains a polymer electrolyte and / or a gel electrolyte. Since the second solid electrolyte layer contains a polymer electrolyte and / or a gel electrolyte, it is relatively flexible and can follow the expansion and contraction accompanying the charge and discharge of the positive electrode layer containing sulfur, thereby suppressing short circuits. Furthermore, since the first solid electrolyte contains a sulfide solid electrolyte, it is possible to reduce the barrier to lithium insertion into the positive electrode layer, thereby enabling the lithium-sulfur battery to obtain a high battery capacity.
[0073] <<Method of manufacturing lithium-sulfur batteries>> The lithium-sulfur battery of the present disclosure can be manufactured by a manufacturing method including the following steps. laminating a preliminary positive electrode layer containing sulfur and a sulfide containing phosphorus and sulfur, the first solid electrolyte layer, the second solid electrolyte layer, and the negative electrode layer in this order to form a preliminary laminate; A discharge operation is performed on the preliminary laminate, whereby a part of the sulfur in the preliminary positive electrode layer, as well as a sulfide containing phosphorus and sulfur elements, are reacted with lithium to produce a sulfide solid electrolyte, thereby forming the positive electrode layer.
[0074] <Formation of preliminary laminate> laminating a preliminary positive electrode layer containing sulfur and a sulfide containing elemental phosphorus and elemental sulfur, the first solid electrolyte layer, the second solid electrolyte layer, and the negative electrode layer in this order to form a preliminary laminate.
[0075] <Reserve positive electrode layer> The spare positive electrode layer includes sulfur and a sulfide containing elemental phosphorus and elemental sulfur.
[0076] (Sulfides containing phosphorus and sulfur) The sulfide has at least phosphorus and sulfur. The spare positive electrode layer may contain only sulfide having phosphorus and sulfur, or may further contain sulfide having other elements (e.g., Ge, Sn, Si, B, or Al) and sulfur. In the latter case, it is preferable that the spare positive electrode layer contains sulfide having phosphorus and sulfur as the main component of the sulfide.
[0077] The sulfide preferably contains an ortho structure of phosphorus. An example of the ortho structure of phosphorus is, but is not limited to, the PS4 structure. The sulfide may contain an ortho structure of M element (M is, for example, Ge, Sn, Si, B, Al, etc.). An example of the ortho structure of M element is, but is not limited to, the GeS4 structure, the SnS4 structure, the SiS4 structure, the BS3 structure, the AlS3 structure, etc. On the other hand, the sulfide may contain a sulfide of phosphorus element (for example, P2S5). The sulfide may be a sulfide of M element (M x S y ), where x and y are integers that provide electrical neutrality with S depending on the type of M. x S y) may be, for example, GeS2, SnS2, SiS2, B2S3, Al2S3, etc., but is not limited to these.
[0078] The sulfur element in the sulfide and the sulfur element in the elemental sulfur or sulfur compound as the positive electrode active material may have a chemical bond (SS bond). In particular, it is preferable that the sulfur element in the ortho structure and the sulfur element in the elemental sulfur as the positive electrode active material have a chemical bond (SS bond).
[0079] In the preliminary positive electrode layer, the molar ratio of phosphorus element to sulfur element (phosphorus element / sulfur element) is not particularly limited, but may be 0.03 or more, 0.06 or more, 0.09 or more, or 0.12 or more, and may be 0.50 or less, 0.30 or less, or 0.27 or less. The denominator of the molar ratio (phosphorus element / sulfur element) means the amount of all sulfur elements contained in the preliminary positive electrode layer. In the present disclosure, since both the positive electrode active material and the sulfide contain sulfur element, it is the total amount of sulfur element in both.
[0080] (Lithium element in spare electrode layer) The preliminary positive electrode layer may be substantially free of lithium element. "Substantially free of lithium element" means that the ratio of lithium element to all elements contained in the preliminary positive electrode layer is 20 mol% or less. The ratio of lithium element may be 15 mol% or less, 10 mol% or less, 5 mol% or less, or 1 mol% or less.
[0081] A cathode composite containing a solid electrolyte having lithium element is known. For example, when a solid electrolyte using Li2S as a raw material is used, the capacity of a battery using such a cathode composite in a cathode layer tends to be low due to the low water resistance of Li2S. In contrast, when the spare cathode layer in the manufacturing method of the lithium-sulfur battery disclosed herein does not substantially contain a lithium element (e.g., Li2S), the capacity reduction of the lithium-sulfur battery can be suppressed.
[0082] For the first solid electrolyte layer, the second solid electrolyte layer, and the negative electrode layer, reference can be made to the above description of "Configuration of Lithium-Sulfur Battery."
[0083] The method for forming the preliminary laminate is not particularly limited, but specifically, for example, a first solid electrolyte layer is superimposed on a preliminary positive electrode layer and pressed to obtain a laminate of the preliminary positive electrode layer and the first solid electrolyte layer, and then a second solid electrolyte layer and a negative electrode layer are laminated in this order on the first solid electrolyte layer of this laminate, and the positive and negative electrode terminals are connected and sealed with a laminate film.
[0084] <Formation of Positive Electrode Layer> The method for producing a lithium-sulfur battery of the present disclosure may include performing a discharge operation on the preliminary laminate to react a part of sulfur in the preliminary positive electrode layer and a sulfide containing phosphorus and sulfur elements with lithium to produce a sulfide solid electrolyte, thereby forming the positive electrode layer.
[0085] (discharge operation) The discharge operation can be performed in a temperature environment of 60° C. or higher, but is not particularly limited thereto. The temperature environment may be 80° C. or higher, or 100° C. or higher, or may be 200° C. or lower. Note that the discharge operation is usually performed on the pre-laminate when the surface temperature of the pre-laminate is the same as the environmental temperature.
[0086] The discharge rate in the discharging operation is not particularly limited, and may be, for example, 0.01C or more, 0.05C or more, or 0.10C or more, and may be 0.50C or less, or 0.33C or less.
[0087] When performing the discharging operation, the preliminary electrode laminate may be restrained, and the preliminary electrode layer may be restrained at, for example, 1 MPa, but is not limited to this case.
[0088] The sulfide preferably serves as an ion conduction path during charging and discharging. During discharging, lithium ions are conducted from the negative electrode layer through the second solid electrolyte and the first solid electrolyte to the preliminary positive electrode layer, and the lithium ions that reach the preliminary positive electrode layer react with the positive electrode active material. When no sulfide is present in the preliminary positive electrode layer, the ion conductivity of the discharge product of sulfur as the positive electrode active material (e.g., Li2S) is low, so that the ion conduction path in the preliminary positive electrode layer is insufficient, and the discharge reaction is difficult to proceed. On the other hand, when sulfide is present in the preliminary positive electrode layer, even if the ion conductivity of the discharge product of sulfur as the positive electrode active material (e.g., Li2S) is low, the ion conduction path in the preliminary positive electrode layer is secured by the sulfide, so that the discharge reaction is easy to proceed. EXAMPLES
[0089] The present disclosure will be described in more detail with reference to the following examples, but the scope of the present disclosure is not limited to these examples.
[0090] Example 1 <Preparation of preliminary positive electrode layer> Sulfur (S) (42 parts by mass) as a positive electrode active material, diphosphorus pentasulfide (P2S5) (23 parts by mass) as a sulfide containing phosphorus and sulfur elements, and vapor grown carbon fiber (VGCF) (35 parts by mass) as a conductive assistant were mixed by a ball mill. The obtained mixed powder was put into a polypropylene (PP) container, and a 5% by mass mesitylene solution of a styrene-based binder as a binder and mesitylene were added, and the mixture was dispersed for 30 seconds with an ultrasonic dispersion device (UH-50 manufactured by SMT Co., Ltd.), and then shaken for 30 minutes with a shaker (TTM-1 manufactured by Shibata Scientific Co., Ltd.) to prepare a preliminary positive electrode composite slurry. The obtained preliminary positive electrode composite slurry was applied to an aluminum (Al) foil as a positive electrode current collector by a blade method using an applicator to a basis weight of 7.6 mg / cm. 2 The mixture was then naturally dried and then dried on a hot plate heated to 100° C. for 30 minutes to obtain a preliminary positive electrode layer formed on the Al foil.
[0091] (Preparation of sulfide solid electrolyte layer) The L2S-P2S5-based glass ceramics containing lithium iodide (LiI) were mixed by a ball mill and sintered to obtain a sulfide solid electrolyte. The obtained sulfide solid electrolyte was then placed in a PP container, and a 5% by mass heptane solution of a butylene rubber-based binder as a binder and heptane were added, and the mixture was dispersed for 30 seconds using an ultrasonic dispersion device (UH-50 manufactured by SMT Co., Ltd.), and then shaken for 30 minutes using a shaker (TTM-1 manufactured by Shibata Scientific Co., Ltd.) to prepare a sulfide solid electrolyte mixture slurry. The sulfide solid electrolyte mixture slurry was applied onto a PET film by the blade method using an applicator, naturally dried, and dried for 30 minutes on a hot plate heated to 100°C to obtain a coating film formed on the PET film. The coated surfaces of the coating film formed on the PET film were overlapped and pressed at 7 tons, and then the PET film was peeled off to obtain a sulfide solid electrolyte layer.
[0092] Preparation of Polymer Electrolyte Layer Polyethylene oxide (PEO) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were dissolved in acetonitrile. Here, the molar ratio (EO / Li) of the C2H5O unit (EO unit) of the polyethylene oxide to the lithium (Li) element contained in LiTFSI was adjusted to be EO / Li=20 / 1 (molar ratio). Benzoyl peroxide (BPO) as an initiator was added to this solution in an amount of 10 mass% relative to the total amount of PEO and LiTFSI, and the solution was stirred until it became a homogeneous solution, to prepare a polymer electrolyte layer precursor solution. Next, the polymer electrolyte layer precursor solution was applied onto a polyethylene terephthalate (PET) film by a blade method using an applicator, dried on a hot plate heated to 100°C for 30 minutes, and then the PET film was peeled off to obtain a polymer electrolyte layer.
[0093] <Preparation of preliminary laminate A1> Metallic lithium as the negative electrode layer was punched to φ13.00 mm. In the same manner, the polymer electrolyte layer and the sulfide solid electrolyte layer were punched to φ14.50 mm, and the preliminary positive electrode layer was punched to φ11.28 mm. The sulfide solid electrolyte layer as the first solid electrolyte layer was superimposed on the circular preliminary positive electrode layer, and then pressed at 7 tons to obtain a laminate of the preliminary positive electrode layer and the sulfide solid electrolyte layer. On the sulfide solid electrolyte layer of this laminate, a polymer electrolyte layer as the second solid electrolyte layer and metallic lithium as the negative electrode layer were laminated in this order, and the positive and negative electrode terminals were connected and sealed with a laminate film to obtain a preliminary laminate A1.
[0094] <Preparation of lithium-sulfur battery B1 and electrochemical evaluation> The preliminary laminate A1 was restrained with a metal plate at a pressure of 1 MPa. Then, it was placed in a thermostatic chamber at 60°C and a constant current (0.06 mA / cm2) was applied in a cutoff voltage range of 1.2 to 3.1 V. 2 A discharge measurement was performed by the constant current test to obtain a lithium-sulfur battery B1. A charge measurement was then performed under the same constant current conditions. The discharge capacity of the lithium-sulfur battery B1 was 6.3 mAh, the charge capacity was 5.0 mAh, and no short circuit occurred.
[0095] Comparative Example 1 <Preparation of preliminary laminate a1, preparation of lithium-sulfur battery b1, and electrochemical evaluation> Metallic lithium as the negative electrode layer was punched to φ13.00 mm. Similarly, the sulfide solid electrolyte layer was punched to φ14.50 mm, and the preliminary positive electrode layer was punched to φ11.28 mm. The circular preliminary positive electrode layer was pressed with 7 tons, and a sulfide solid electrolyte layer as the first solid electrolyte layer and metallic lithium as the negative electrode layer were laminated thereon in this order, and the positive and negative electrode terminals were connected and sealed with a laminate film to obtain a preliminary laminate a1. The preliminary laminate a1 is a laminate that does not include a polymer electrolyte layer, which is the second solid electrolyte layer, compared to the preliminary laminate A1. The electrochemical evaluation of the preliminary laminate a1 was performed in the same manner as the electrochemical evaluation of the preliminary laminate A1, and a lithium-sulfur battery b1 was obtained. The discharge capacity of the lithium-sulfur battery b1 was 6.3 mAh, but the charge capacity could not be obtained because a short circuit occurred.
[0096] Comparative Example 2 <Preparation of preliminary laminate a2, preparation of lithium-sulfur battery b2, and electrochemical evaluation> Metallic lithium as the negative electrode layer was punched to φ13.00 mm. Similarly, the polymer electrolyte layer was punched to φ14.50 mm, and the preliminary positive electrode layer was punched to φ11.28 mm. The circular preliminary positive electrode layer was pressed with 7 tons, and a polymer electrolyte layer as the second solid electrolyte layer and metallic lithium as the negative electrode layer were laminated thereon in this order, and the positive and negative electrode terminals were connected and sealed with a laminate film to obtain a preliminary laminate a2. The preliminary laminate a2 is a laminate that does not include a sulfide solid electrolyte layer, which is the first solid electrolyte layer, compared to the preliminary laminate A1. The electrochemical evaluation of the preliminary laminate a2 was performed in the same manner as the electrochemical evaluation of the preliminary laminate A1, and a lithium-sulfur battery b2 was obtained. The discharge capacity of the lithium-sulfur battery b2 was 1.3 mAh, the charge capacity was 0.8 mAh, and no short circuit occurred.
[0097] Table 1 shows the electrochemical evaluations of Example 1 and Comparative Examples 1 and 2.
[0098] [Table 1]
[0099] The lithium-sulfur battery b1 performed well in the initial discharge test, but a short circuit occurred during the charge test after the discharge test. It is speculated that the cause of the short circuit in the lithium-sulfur battery b1 was that the sulfide solid electrolyte layer could not keep up with the expansion of the positive electrode layer containing sulfur during the discharge test, which caused cracks in the layer, which led to the precipitation of lithium during the subsequent charge process.
[0100] The lithium-sulfur battery b2 did not short circuit, but the initial discharge capacity was significantly reduced. This is presumably because there was a barrier to lithium insertion from the polymer electrolyte layer to the positive electrode layer containing sulfur, which prevented the positive electrode active material and lithium from sufficiently intercalating.
[0101] On the other hand, the lithium-sulfur battery B1 performed well in the initial discharge measurement, obtaining a discharge capacity of 6.3 mAh, and also obtaining a charge capacity of 5.0 mAh in the charge measurement after the discharge measurement, without the occurrence of a short circuit. From the above, it became clear that by disposing a sulfide solid electrolyte between the sulfur-containing positive electrode layer and the polymer electrolyte layer, it is possible to suppress short circuits caused by charge and discharge, and to obtain a high battery capacity.
[0102] While preferred embodiments of the disclosed lithium-sulfur batteries and methods of manufacturing lithium-sulfur batteries have been described, those skilled in the art will recognize that modifications can be made without departing from the scope of the claims. [Explanation of symbols]
[0103] 100 Lithium-sulfur battery 110 Positive electrode layer 210 First solid electrolyte layer 220 Second solid electrolyte layer 310 Negative electrode layer
Claims
1. 1. A lithium-sulfur battery, comprising: the lithium-sulfur battery has a positive electrode layer, a first solid electrolyte layer, a second solid electrolyte layer, and a negative electrode layer in this order; The first solid electrolyte layer includes a sulfide solid electrolyte; and The second solid electrolyte layer comprises a polymer electrolyte and / or a gel electrolyte; Lithium-sulfur battery.
2. The negative electrode layer has a negative electrode current collector layer, and 2. The lithium-sulfur battery according to claim 1, wherein lithium ions transferred from the positive electrode layer during charging are precipitated as metallic lithium between the second solid electrolyte layer and the negative electrode current collector layer.
3. 10. The lithium-sulfur battery of claim 1 , wherein the second solid electrolyte layer comprises a polymer electrolyte.
4. 4. The lithium-sulfur battery of claim 3, wherein the polymer electrolyte comprises polyethylene oxide.
5. A method for producing the lithium-sulfur battery according to any one of claims 1 to 4, comprising the steps of: laminating a preliminary positive electrode layer containing sulfur and a sulfide containing phosphorus and sulfur elements, the first solid electrolyte layer, the second solid electrolyte layer, and the negative electrode layer in this order to form a preliminary laminate; A discharge operation is performed on the preliminary laminate, whereby a part of the sulfur in the preliminary positive electrode layer, and a sulfide containing phosphorus and sulfur elements, are reacted with lithium to produce a sulfide solid electrolyte, thereby forming the positive electrode layer.
Citation Information
Patent Citations
Lithium-sulfur battery
JP2019526897A
Solid state battery
JP2021190339A
Solid electrolyte sheet, method for manufacturing same, and solid-state battery equipped with same
WO2023190547A1
All-solid battery and manufacturing method thereof
JP2023009988A
Cited By
Wearable display clothing
JP7746626B1